The Neodymium Stable Isotope Composition of the Oceanic Crust: Reconciling the Mismatch Between Erupted Mid-Ocean Ridge Basalts and Lower Crustal Gabbros - McCoy-West, Alex J.; Millet, Marc-Alban; Burton, Kevin W. (Frontiers in Earth Science, 2020)
The trace element and isotopic compositions of mid-ocean ridge basalts (MORB) provide an important cornerstone for all studies seeking to understand mantle evolution. Globally there is a significant over-enrichment in the incompatible trace element concentrations of MORB relative to levels which should be generated by fractional crystallization. Thermal and geochemical constraints suggest that MORB require generation in open system magma chambers. However, the petrology of lower oceanic crustal rocks suggests instead that these enrichments maybe formed through reactive porous flow (RPF). Stable isotope compositions are process dependent and therefore provide an excellent mechanism to compare these contrasting models. This study presents the first neodymium (Nd) stable isotope compositions of Indian MORB and well characterized gabbroic rocks from the lower oceanic crust sampled at the Southwest Indian Ridge (SWIR) (Hole 735B). Indian MORB is extremely homogenous with a mean δ146Nd of −0.025 ± 0.005‰ which is identical to the composition of Pacific MORB. Despite significant variability in the source composition of MORB globally (i.e., 143Nd/144Nd) their indistinguishable δ146Nd compositions suggests δ146Nd was homogenized through a consistent process (i.e., repeated melt addition in the open-system magma chambers across the global ridge network). In stark contrast, oceanic gabbros have δ146Nd ranging from −0.026 to −0.127‰, doubling the natural variability in Nd stable isotopes observed in terrestrial rocks. Clinopyroxene separates possess variable δ146Nd but are isotopically heavier than the gabbroic whole rocks at the same major element compositions. These large variations in δ146Nd cannot be generated solely by the fractionation or accumulation of magmatic minerals. Hole 735B preserves widespread evidence of RPF which could induce kinetic isotope fractionation during crystal growth. However, the maximum kinetic isotope fractionations that can be generated in clinopyroxene are only ca. 0.02‰, therefore several cycles of dissolution and reprecipitation of isotopic signatures at grain boundaries are required to explain the range of δ146Nd observed in the gabbros. The large disconnect between the average composition of the oceanic crust (δ146Nd = −0.067‰) and MORB, combined with limited evidence of melt extraction to the upper crust at Hole 735B, led to the conclusion that melts involved in RPF have not contributed in a substantial way to the Nd isotope composition of erupted MORB.